Effects of culinary herbs and spices on obesity: A systematic literature review of clinical trials - Chandana Deekshith; Markandeya Jois; Jessica Radcliffe; Jency Thomas (Journal of Functional Foods, 2021)
The aim of this article was to systematically review literature on clinical trials investigating the effects of culinary herbs and spices on obesity in adults. Relevant articles were searched through the electronic databases using predefined search terms. Thirty commonly used herbs and spices for weight loss were selected based on the literature. Out of 33 intervention studies that were eligible for inclusion in the review, 24 studies reported statistically significant (P < 0.05) reductions in obesity indices either compared to baseline or to the placebo. Overall, eight herbs/spices were reported to be beneficial in regards to obesity in the eligible literature including basil (on BW and BMI), cardamom (on BW, BMI and WC), cinnamon (on BW, BMI, BFP and WC), coriander (on BMI), garlic (on BMI and WC), ginger (on BW, BMI, WC and HC), nigella (on BW, BMI, WC, BFP and HC) and turmeric (on BW, BMI, BFP and WC).